Konsep Pembenaran Menurut Roma 5:1-11 Suatu Studi Eksegesis - Hia, Martini; Bastanta, Dedi; Tambunan, Parsaoran (STT Injili Indonesia Medan, 2023)
One of the worst consequences of the man's fall into the sin is death. The first humans, Adam and Eve, after violating God's command by eating the fruit of the tree in the middle of the garden of Eden, made them violate God's commandment (sinful), this violation has brought the heaviest punishment, namely death for that human. The Lord God is faithful and infinite justice to what He has said, giving rewards, life to everyone who sincerely does His will and carries out the punishment, death for everyone who violates His word. But the Lord God in all His omniscience (providensia) along with the passage of time and His design, has determined the only way and rule for everyone to be justified before God, is If you declareÂ with your mouth, â€œJesus is Lord,â€Â and believeÂ in your heart that God raised him from the dead,Â you will be saved (Romans 10:9-10), He is a real form of God who is Loving and has come into the world (Incarnation), He has sacrificed / died on the cross and rose from the grave on the third day to save mankind, then the sinner has the status of